2021
DOI: 10.2196/24177
|View full text |Cite
|
Sign up to set email alerts
|

Using a Commercially Available App for the Self-Management of Hypertension: Acceptance and Usability Study in Saudi Arabia

Abstract: Background The use of smartphone apps to assist in the self-management of hypertension is becoming increasingly common, but few commercially available apps have the potential to be effective along with adequate security and privacy measures in place. In a previous study, we identified 5 apps that are potentially effective and safe, and based on the preferences of doctors and patients, one (Cora Health) was selected as the most suitable app for use in a Saudi context. However, there is currently no … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 53 publications
2
17
0
1
Order By: Relevance
“…Accordingly, a qualitative study by Morrissey et al [ 53 ] also highlighted concerns regarding the risks of health apps used to improve medication adherence and the need for promote eHealth literacy among hypertensive patients. Regarding the real-world assessment of apps, a mixed methods study by Allessa et al [ 34 ] showed that apps for self-management of hypertension can be functional and acceptable to users, but they can also be considerably improved through training [ 34 ], which corresponds to UTAUT determinants like performance and effort expectancy as well as facilitating conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, a qualitative study by Morrissey et al [ 53 ] also highlighted concerns regarding the risks of health apps used to improve medication adherence and the need for promote eHealth literacy among hypertensive patients. Regarding the real-world assessment of apps, a mixed methods study by Allessa et al [ 34 ] showed that apps for self-management of hypertension can be functional and acceptable to users, but they can also be considerably improved through training [ 34 ], which corresponds to UTAUT determinants like performance and effort expectancy as well as facilitating conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Patients and physicians differ in several aspects regarding their acceptance of hypertension apps, especially based on their motivations or reasons to use these apps. For patients, the focus is on managing their own disease to avoid health deterioration [ 12 , 34 ]. Thus, acceptance of health apps crucially depends on whether disease-specific needs are met [ 12 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings are in line with prior research, which has found that older users may be less engaged and/or experience greater issues with technological interventions. 22–24 Some concerns were raised by healthcare professionals regarding app accessibility, for example, the lack of a zoom feature and inability to change font sizes, which may hinder older people or people with impaired vision. Whilst these accessibility issues are likely to affect older people disproportionately, this population also has a higher frequency of underlying health conditions, meaning they are less likely to donate blood anyway.…”
Section: Discussionmentioning
confidence: 99%
“…In the meantime, training could enable older users to engage more with this app, and other e-health technologies. 22 , 26 Ouhbi et al showed that very few donation apps are available in multiple languages, limiting the number of potential donors they can reach. 14 , 15 The present research also found that widening the language provision of the Wateen app beyond Arabic and English could increase its accessibility and user base.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation